Long-Term Neurodevelopmental Outcome Measures in Preterm Infants: A Systematic Review - Nurul Purnamasari; Ririn Azhari (The International Journal of Medical Science and Health Research, 2025)
Introduction: Advances in neonatal care have significantly increased the survival of preterm infants, shifting the focus to long-term neurodevelopmental outcomes. Infants born before 37 weeks of gestation are at an elevated risk for a wide spectrum of impairments due to the interruption of critical in-utero brain development. This systematic review synthesizes the current evidence on long-term neurodevelopmental outcomes in preterm infants and the measures used for their assessment. Methods: This review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search of MEDLINE, Embase, CINAHL, PsycINFO, Scopus, Web of Science, and the Cochrane Library was performed to identify observational studies and randomized controlled trials that reported neurodevelopmental outcomes in preterm infants assessed at or after 12 months of age, compared to term-born controls or other preterm subgroups. Two independent reviewers performed study selection, data extraction, and risk of bias assessment using the Cochrane Risk of Bias 2 (RoB 2) tool for randomized trials and the Newcastle-Ottawa Scale for observational studies. A narrative synthesis was conducted, with results grouped by neurodevelopmental domain. Results: The search yielded 4,720 unique records, from which 8 studies met the inclusion criteria, encompassing a total of 72,974 preterm-born children. The evidence confirms a clear gradient of risk, with the prevalence and severity of impairment increasing with decreasing gestational age. Preterm infants demonstrate significantly higher rates of adverse outcomes across all major domains. Key findings include a pooled prevalence of overall neurodevelopmental impairment of 16% and cerebral palsy of 5% in low- and middle-income countries. Cognitive delays were the most frequently reported outcome, with preterm children scoring, on average, 11-13 points lower on IQ scales than their term-born peers. Increased risks were also consistently found for motor impairments, language delays, academic difficulties, attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), and internalizing and externalizing behavioral problems. A wide array of assessment tools was identified, with the Bayley Scales of Infant and Toddler Development and Wechsler Intelligence Scales being the most common. Discussion: The findings underscore the substantial and persistent burden of neurodevelopmental morbidity following preterm birth. The heterogeneity of assessment tools across studies presents a significant challenge for synthesizing evidence and comparing outcomes. The data suggest a developmental cascade, where early motor and language deficits may contribute to later cognitive and behavioral challenges. The necessity for long-term surveillance is highlighted by "sleeper effects," where some impairments only manifest later in childhood as academic and social demands increase. Conclusion: Preterm birth is a major risk factor for a wide spectrum of long-term neurodevelopmental impairments. Comprehensive, multidisciplinary follow-up programs using validated and context-appropriate assessment tools are essential for early identification and intervention to optimize the developmental potential of this vulnerable population.